New species of Afrotropical Muscidae (Diptera: Muscoidea) - Couri, Márcia; Pont, Adrian C. (Zootaxa, 2014)
The study of recently collected Afrotropical Muscidae (Diptera) from Burundi, Democratic Republic of the Congo, Kenya and South Africa has revealed ten new species which are described herein: Coenosia duomaculata sp. nov., C. nigromaculata sp. nov., C. fragilis sp. nov., Helina harrisorum sp. nov., H. ferfriniorum sp. nov., Hydrotaea tantula sp. nov., Limnophora diminuta sp. nov., L. antennalis sp. nov., Spilogona brunnea sp. nov. and S. bella sp. nov. Coenosia, Helina and Limnophora are speciose muscid genera, found throughout the Afrotropical Region, while Hydrotaea and Spilogona have a more restricted geographic distribution and include some 20 species each.